(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Researchers are looking for ways to protect the bones of people with diabetes and high blood pressure. The focus of this research was on hepatocyte growth factor (HGF), which is a natural molecule in the body that regulates the growth process. Also, this molecule plays a role in bone reproduction, changing its shape and creating a balance between osteoblast and osteoclast. But what was unknown about this molecule until now is that the HGF molecule also affects the chemical structure of bones. In order to investigate these effects, HGF molecules were injected into diabetic rats with high blood pressure and then, using a spectroscopic technique, they analyzed the chemical structure of the bones of these rats. As a result, it was found that soluble phosphate in bones increases with HGF intake. This important change shows that HGF molecules can stimulate the process of bone regeneration in response to diabetes, high blood pressure and drugs used to treat these diseases. In osteoporosis, the bones become porous. The microscopic structure of bones is honeycomb. Pores and houses in cancellous bone are much larger than healthy bone. In this case, the bones gradually lose their mass and density and become very sensitive and fragile. Bones are composed of collagen fibers and minerals. From birth to early 20s, bone cells grow and thicken by absorbing nutrients and minerals. Usually, the peak of bone density is at the age of 20. Bone growth and development continues until about 25 years of age and rarely slows down thereafter. After the age of 45 and with increasing age, the bone density gradually decreases and the calcium required for the body is supplied from the bones. Decrease in bone density with age is completely normal; But some factors accelerate this process. Inactivity, reduction of vitamin D in the body, suffering from certain diseases such as cancer, premature menopause, reduction of estrogen in the body and certain medical conditions such as hyperthyroidism, celiac disease, chronic kidney failure, rheumatoid arthritis, chronic liver diseases and type one diabetes are the most important are the risk factors of the disease. The use of special drugs such as steroid, hormonal, anticonvulsant and antidepressant drugs are among the most important drugs that reduce bone density.